Kulimlim ([Quezon City] Viva Fils, 2004)
The past has come to haunt Jake Cabrera. Based on technicality, the Supreme Court has ordered the release of the three men convicted of raping his wife after eight years inprison. Jake decides to render his own brand of justice and seeks the help of a retired colonel. But something horrifying happens along the way. Now his family is forced to deal with the terror that has entered their home.
VCD
Robin Padilla, Tanya Garcia
Keywords: Horror films; Feature films